Clinical patterns, recovery time and prolonged impact of COVID-19 illness in international athletes: the UK experience - Hull, J. H.; Wootten, M.; Moghal, M.; Heron, N.; Martin, R.; Walsted, E. S.; Biswas, A.; Loosemore, M.; Elliott, N.; Ranson, C. (British Journal of Sports Medicine, 2022)
Objectives: To report COVID-19 illness pattern, symptom duration and time loss in UK elite athletes.